Christo works 1958-1983 - Nakahara, Yusuke (Tokio : Sogetsu Shuppan, 1984)
Volz, Wolfgang Shunk-Kender Eeva-Inkeri Gorgoni, Gianfranco Shunk, Harry Christo, Jeanne-Claude Eva-Glunz de Deynes, Raymond O'Malley, Maureen Cugini, Thomas de Jager, Ab Grossman, André Planten, Angelika Rouget, Bernard Lauritzen, Bruce Boesch, Ferdinand Lajoux, J.D. Baum, Klaus Bertholo, René Unruh, Roland Anzai, Shigeo Wewerka, Stephan
boek
Keywords: Christo